2017
DOI: 10.1002/lary.26714
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for short‐ and long‐term hearing preservation in cochlear implantation with conventional‐length electrodes

Abstract: 4. Laryngoscope, 128:482-489, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 43 publications
4
65
0
Order By: Relevance
“…The probability of functional improvement after cochlear implantation also decreases with more hearing in the ear to be implanted, particularly as the pre-implant word perception score for this ear approaches the mean post-operative performance with a cochlear implant [35]. Despite improvement in hearing preservation techniques during implantation, the surgery is likely to reduce or eliminate any residual hearing in the ear to be implanted [36][37][38]. When there is significant useful speech perception in either ear, careful consideration is needed on an individual basis with regard to probability of benefit, and risk of losing residual hearing in the implanted ear.…”
Section: Speech Perception Improvement (Efficacy)mentioning
confidence: 99%
“…The probability of functional improvement after cochlear implantation also decreases with more hearing in the ear to be implanted, particularly as the pre-implant word perception score for this ear approaches the mean post-operative performance with a cochlear implant [35]. Despite improvement in hearing preservation techniques during implantation, the surgery is likely to reduce or eliminate any residual hearing in the ear to be implanted [36][37][38]. When there is significant useful speech perception in either ear, careful consideration is needed on an individual basis with regard to probability of benefit, and risk of losing residual hearing in the implanted ear.…”
Section: Speech Perception Improvement (Efficacy)mentioning
confidence: 99%
“…This localized stimulation provides superior place-pitch spectral discrimination [15,16], and improved speech perception outcomes [17,18]. However, due to their increased stiffness and size, perimodiolar arrays which use stylets to keep them straight at the point of insertion, have been associated with poorer hearing preservation results and a higher incidence of basilar membrane trauma compared to thin, flexible lateral wall arrays [19,20]. The CI532 does not have a stylet and is introduced into the cochlea using a new deployment method called advance-throughthe-sheath.…”
Section: Introductionmentioning
confidence: 99%
“…Wanna et al performed a retrospective study of 196 patients (225 implants, mean age at time of CI 63.7 years) looking at hearing preservation, which they defined as a postoperative air-conduction threshold <= 80 dB hearing loss (HL) at 250 Hz. 2 They found that LW electrodes were more likely to preserve functional hearing when compared to PM electrodes at both short-term (2-3 weeks postoperative) and long-term (>1 year postoperative) follow-up. Although MS electrodes had 3.4 times higher odds of hearing preservation when compared to PM arrays in the short term, there was no significant difference between these two in the long term.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Other studies have specifically compared which electrode type is better at preserving low‐frequency hearing. Wanna et al performed a retrospective study of 196 patients (225 implants, mean age at time of CI 63.7 years) looking at hearing preservation, which they defined as a postoperative air‐conduction threshold < = 80 dB hearing loss (HL) at 250 Hz . They found that LW electrodes were more likely to preserve functional hearing when compared to PM electrodes at both short‐term (2–3 weeks postoperative) and long‐term (>1 year postoperative) follow‐up.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation